The impact of corporate governance in the promotion of business ethics A prospective study in a sample of private banks - حمود سعد علي; داود فضيلة سلمان (Journal of Economics and Administrative Sciences, 2012)
The study aims to know the role of governance in the consolidation of the principles of business ethics, through the application of the principles of governance and the dimensions of business ethics in the private sector. And knowledge of the validity of the hypothesis key of the current study according to which "increases the ethics of business organizations strength and coherence in the presence of the principles of governance" as it was distributed the questionnaire to a sample of a chairman and board members and managers department and heads of sections in some of the private banks. I have been using correlation analysis and regression testing (t) to see the moral differences and to find out the correlation between the main and branch variables and the impact of principles on every dimension of business ethics. The study found that there is an active role for the Governor of the company in the ethics of the banking sector, it is found that there is the promotion and support for the application of principles of governance in its business, and this was confirmed by hypothesis the main effect that increases the ethics of business organizations the power and coherence in the presence of the principles of governance "